The entring book of Roger Morrice, 1677-1691, Volume VII: Index - Morrice, Roger 1628-1702 (Boydell & Brewer, 2009)
Index to the acclaimed six-volume set of The Entring Book of Roger Morrice
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Keywords: Morrice, Roger / 1628-1702 / Diaries; Clergy / England / Diaries; Diarists / Great Britain / Biography; Great Britain / Politics and government / 1660-1714 / Sources; Great Britain / History / 1660-1714 / Sources; Great Britain / Social life and customs / 17th century / Sources